Complex Large-Bore Radial percutaneous coronary intervention: rationale of the COLOR trial study protocol. Issue 7 (20th July 2020) - Meijers, Thomas A; Aminian, Adel; Teeuwen, Koen; van Wely, Marleen; Schmitz, Thomas; Dirksen, Maurits T; van der Schaaf, Rene J; Iglesias, Juan F; Agostoni, Pierfrancesco; Dens, Joseph; Knaapen, Paul; Rathore, Sudhir; et al.
Abstract : Introduction: The radial artery has become the standard access site for percutaneous coronary intervention (PCI) in stable coronary artery disease and acute coronary syndrome, because of less access site related bleeding complications. Patients with complex coronary lesions are under-represented in randomised trials comparing radial with femoral access with regard to safety and efficacy. The femoral artery is currently the most applied access site in patients with complex coronary lesions, especially when large bore guiding catheters are required. With slender technology, transradial PCI may be increasingly applied in patients with complex coronary lesions when large bore guiding catheters are mandatory and might be a safer alternative as compared with the transfemoral approach. Methods and analysis: A total of 388 patients undergoing complex PCI will be randomised to radial 7 French access with Terumo Glidesheath Slender (Terumo, Japan) or femoral 7 French access as comparator. The primary outcome is the incidence of the composite end point of clinically relevant access site related bleeding and/or vascular complications requiring intervention. Procedural success and major adverse cardiovascular events up to 1 month will also be compared between both groups. Ethics and dissemination: Ethical approval for the study was granted by the local Ethics Committee at each recruiting center ('Medisch Ethische Toetsing Commissie Isala Zwolle', 'Commissie voor medische ethiek ZNA', 'Comité Medische Ethiek Ziekenhuis Oost-Limburg', 'Comité d'éthique CHU-Charleroi-ISPPC', 'Commission cantonale d'éthique de la recherche CCER-Republique et Canton de Geneve', 'Ethik Kommission de Ärztekammer Nordrhein' and 'Riverside Research Ethics Committee'). The trial outcomes will be published in peer-reviewed journals of the concerned literature. Trial registration number: NCT03846752 .